2020
DOI: 10.1002/hbm.24983
|View full text |Cite
|
Sign up to set email alerts
|

Connecting EEG signal decomposition and response selection processes using the theory of event coding framework

Abstract: The neurophysiological mechanisms underlying the integration of perception and action are an important topic in cognitive neuroscience. Yet, connections between neurophysiology and cognitive theoretical frameworks have rarely been established. The theory of event coding (TEC) details how perceptions and actions are associated (bound) in a common representational domain (the “event file”), but the neurophysiological mechanisms underlying these processes are hardly understood. We used complementary neurophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

28
143
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 84 publications
(175 citation statements)
references
References 99 publications
(299 reference statements)
28
143
3
1
Order By: Relevance
“…Until now, the neural mechanisms underlying event file binding effects have extensively been investigated in visuo-motor paradigms using EEG and fMRI methods [13][14][15][16][17][18] . These studies support central aspects of TEC 11,12 using different types of stimuli like pictures of objects and faces requiring different actions (e.g., finger or facial responses). A study considering the TEC investigated the neurophysiological basis of distractor-response binding mechanisms in the visual domain using letter stimuli and found that event files but not object or action files are modulated by stimulus-response interactions 11 .…”
supporting
confidence: 65%
See 4 more Smart Citations
“…Until now, the neural mechanisms underlying event file binding effects have extensively been investigated in visuo-motor paradigms using EEG and fMRI methods [13][14][15][16][17][18] . These studies support central aspects of TEC 11,12 using different types of stimuli like pictures of objects and faces requiring different actions (e.g., finger or facial responses). A study considering the TEC investigated the neurophysiological basis of distractor-response binding mechanisms in the visual domain using letter stimuli and found that event files but not object or action files are modulated by stimulus-response interactions 11 .…”
supporting
confidence: 65%
“…Since P1 and N1 components constitute early electrophysiological responses to sensory stimulus modulations, stimulus-response association processes were not expected to be reflected by these components. Also, previous findings on event file binding processes did not show modulations in these ERP-components 12 . This is in line with theoretical conceptions of TEC stating that perceptual properties of stimuli are coded in object files and not in event files 3 which are focus of the current study.…”
mentioning
confidence: 51%
See 3 more Smart Citations